2020
DOI: 10.1002/jbmr.4740
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharide-Induced Bone Loss in Rodent Models: A Systematic Review and Meta-Analysis

Abstract: Osteoporosis has traditionally been characterized by underlying endocrine mechanisms, though evidence indicates a role of inflammation in its pathophysiology. Lipopolysaccharide (LPS), a component of gram‐negative bacteria that reside in the intestines, can be released into circulation and stimulate the immune system, upregulating bone resorption. Exogenous LPS is used in rodent models to study the effect of systemic inflammation on bone, and to date a variety of different doses, routes, and durations of LPS a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 156 publications
0
3
1
Order By: Relevance
“…Interestingly, the anabolic effect of LPS in our model of SCI‐induced intramuscular NHO is in contrast to other reports showing that (i) chronic LPS administration in mice leads to skeletal bone loss, mostly by increasing osteoclastogenesis as recently reviewed in a meta‐analysis, ( 61 ) and (ii) that addition of LPS in cultures of the mouse pro‐osteoblastic immortalized cell line MC3T3‐E1 ( 62 ) or primary calvarial osteoblasts ( 63 ) reduces expression of osteoblasts markers. However, a number of articles have also shown that LPS can have an anabolic effect on mesenchymal progenitor cells isolated from human bone marrow, ( 64 ) umbilical cord blood, ( 65 ) periodontal ligaments, ( 66 ) mouse bone marrow, ( 67 ) and increases expression of osteoblast markers and mineralization.…”
Section: Discussioncontrasting
confidence: 94%
“…Interestingly, the anabolic effect of LPS in our model of SCI‐induced intramuscular NHO is in contrast to other reports showing that (i) chronic LPS administration in mice leads to skeletal bone loss, mostly by increasing osteoclastogenesis as recently reviewed in a meta‐analysis, ( 61 ) and (ii) that addition of LPS in cultures of the mouse pro‐osteoblastic immortalized cell line MC3T3‐E1 ( 62 ) or primary calvarial osteoblasts ( 63 ) reduces expression of osteoblasts markers. However, a number of articles have also shown that LPS can have an anabolic effect on mesenchymal progenitor cells isolated from human bone marrow, ( 64 ) umbilical cord blood, ( 65 ) periodontal ligaments, ( 66 ) mouse bone marrow, ( 67 ) and increases expression of osteoblast markers and mineralization.…”
Section: Discussioncontrasting
confidence: 94%
“…As a major Gram-positive bacteria cell wall component, LTA is related to various in ammatory diseases 22 . With the increased level of LPS in the circulation, systemic in ammation can be activated, which will induce bone loss 23 . Herein, to investigate the underlying correlation between GI and skeletal system after B@S treatment, we veri ed serum LPS and LTA concentration by enzyme-linked immunosorbent assay (ELISA).…”
Section: Engineered Postbiotics Nanoparticles Restored Osteoblastoste...mentioning
confidence: 99%
“…In a murine clavarial model of titanium-induced bone destruction, histological analysis showed that the eroded surface (ES), TRAP-positive multinucleated cells, and Oc.S were increased [26]. Lipopolysaccharides, a surface membrane component of gram-negative bacteria, is another potent inducer of bone resorption, upregulating osteoclast differentiation and its activities [27]. In in vivo studies, the group receiving LPS displayed a higher number of TRAP-positive osteoclasts and expression of osteoclastogenic markers [including RANKL, NFATc1, Fos proto-oncogene (c-Fos), MMP-9, CTSK, and TRAF6], as well as a higher level of inflammatory markers [interleukin-1 beta (IL-1β) and interleukin-6 (IL-6)].…”
Section: In Vivo Evidence On the Role Of Gsk3β On Bone Resorptionmentioning
confidence: 99%